Acceptance of Couples’ HIV Counseling and Testing among Pregnant Women Attending Antenatal Clinic in Likoni sub-County, Mombasa County, Kenya - Makena Mwongera, Jeniffer; Ayieko Yonge, Shadrack; Baya Msanzu, Joseph; Udu Yussuf, Rahma (Multidisciplinary Journal of Technical University of Mombasa, 2021)
Couples’ HIV Counseling and Testing (CHCT) is an essential component of an effective response to AIDS pandemic worldwide and serves as an entry point to HIV care and support. However, it has become increasingly apparent that couples have overlooked the services yet they are too at risk of HIV infection. This study sought to determine level of acceptance of CHCT among pregnant women attending antenatal care services in Likoni sub-County, Mombasa County, Kenya. A descriptive cross-sectional study design was used with structured questionnaires and an observation checklist to collect data from couples while an interview schedule was used to solicit data from health care workers. Results showed uptake of CHCT in the study area was relatively low (33.5%). Statistically significant associations were found between CHCT and demographic factors such as education (χ2 = 29.54; p = 0.005), marital status (χ2 = 12.41; p = 0.010), occupation (χ2 = 18.18; p < 0.001), income (χ2 = 23.02; p < 0.001). In operation factors, statistically significant associations were found between CHCT and distance to health facility (χ2 = 8.31; p = 0.040), means of transport (χ2 = 10.28, p = 0.040), cost of transport (χ2 = 10.92; p = 0.010), appropriateness and convenience of time allocated (χ2 = 11.88, p
Keywords: Antenatal clinic, HIV counselling, Couples testing, Mombasa County, Kenya